Kore Harbi’nde yayınlanan Kutup Yıldızı gazetesi (1950-1955) - Topaloğlu, Soner (My University, 2021)
ÖZETKore Yarımadası, jeopolitik ve jeostratejik açıdan önemli bir konuma sahiptir.Bundan dolayı yarımada, yüzyıllar boyunca bir işgal sahası haline gelmişti. En son iseJaponya tarafından işgal edilmişti. İkinci Dünya Savaşı’nda Kore’yi Japon işgalindenkurtarmak isteyen Sovyet Rusya ve ABD, Kore’yi kuzey güney doğrultusundapaylaşmışlardı. Buna göre Kore’nin 38. Pararel’in kuzeyi Sovyet Rusya, güneyi iseABD’nin kontrolü altına girmişti. Dolayısıyla Kore’nin iki bölgeye ayrılması sürecininilk adımı atılırken yarımadada Sovyet Rusya ile ABD mücadelesi de böylelikle başlamışoldu. Bu süreçte Kuzey Kore ve Güney Kore’de iki farklı hükümet kuruldu.Hükümetlerin kurulmasıyla birlikte iki ayrı bölgede de bir silahlanma yarışı başladı.Sonuç olarak Kuzey Kore Kuvvetleri 25 Haziran 1950’de 38. paraleli geçerek KoreSavaşı’nı başlatmış oldu. Savaşla birlikte Birleşmiş Milletler Kore’de bir güç dengesikurmaya çalışmıştı. Bu maksatla Güney Kore’yi işgalden kurtarmak ve barışı tesisetmek için üye devletlerini Kore’de savaşa davet etmişti. Bu davete cevap verenülkelerden biri de Türkiye Cumhuriyeti idi. Türkiye Kore’de barışın tesis edilmesi içinbaşarılı muharebeler yürütmüştü. Bu muharebeler sırasında personelinin moral vemotivasyonunu artırmak, cephedeki muharebelerden haberdar etmek ve personelineğitimine katkıda bulunmak maksadıyla bir ordu gazetesi çıkarmıştı. Askerî tarihyazımına da kaynaklık edecek olan bu gazete, Kutup YldızıGazetesi idi. Nitekim buçalışmada gazetenin literatüre kazandırılması amaçlanmıştır. Bu kapsamda MSBATASE Arşivi’nde bulunan gazeteler tespit edilmiş, gazetenin nüshaları nitel ve nicelyöntemle analiz edilerek tezin amacına ulaşılmaya çalışılmıştır.

ABSTRACTThe Korean Peninsula has an important geopolitical land geostrategic position.Due to this, the peninsula became an occupation area for centuries. Lastly, it wasoccupied by Japan. In the Second World War, Soviet Russian and the USA, whichwanted to free Korea from Japanese occupation, shared Korea as norther and southregions. Accordingly, the north of Korea's 38th Parallel fell under the control of SovietRussia and the southunder the control of the USA. Therefore, whil the first step towardsthe separation of Koreain to two regions was taken, the conflict betweenthe US andSoviet Russia started in the peninsula as well. In this process, two different states wereestablished as North Korea and South Korea. With the establishment of the states, anarm sracestarted in both regions. Consequently, the North Korean Forces crossed the38th Parallel on June 25, 1950, and started the KoreanWar. Witht hewar, the UnitedNations tried to establish a balance of power in Korea. For this purpose, UN called outits member states to participate in the war in Korea to free South Korea from occupationand to establish peace. One of the countries who responded to this call was the Republicof Turkey. Turkey carried out successful battles to establish peace in Korea. Duringthese battles, Turkish Brigade published an army newspaper to increase the morale andmotivation of its staff, to inform about the battles at the front and to contribute to thetraining of the personnel. This newspaper, which will also serve as a source fo rmilitaryhistoriography, was the Kutup Yldızı Newspaper. As a matter of fact, in this thesis, it isaimed to introducethe newspaper to the literature. In this context, the newspapers foundin the archives of the Ministry of National Defence Archives and Military HistoryDepartment Archive were identified, the copies there of were analysed with qualitativeand quantitative methods and the goal of the thesis wastried to be achieved.
Keywords: Atatürk, Gazi Mustafa Kemal, Türkiye Cum. Bşk., 1, 1881-1938; Atatürk, Mustafa Kemal, President of the Republic of Turkey 1, 1881-1938; BM Ordusu; History; Kore; Kore Harbi; Kore Savaşı, 1950-1953; Kore Türk Tugayı; Korea; Korean War; Korean War, 1950-1953; Kutup Yıldızı gazetesi; KutupYıldızı Gazetesi; KutupYldızı Newspaper; Tarih; Turkey; Turkish Brigade in Korea; Türkiye; UN Forces